Analisis Aplikasi Mobile Transportasi Online Menggunakan User Experience Questionnaire pada Era Milenial dan Z - Abdillah, Leon Andretti (Universitas Diponegoro, 2019)
Online transportation becomes so popular in the ride-sharing industry. Young millennial and z generation users utilize their smartphone not only for communications but also for ordering online transportation services like Gojek. This study examines the experience of millennial and z generation students in using the well-known Gojek online transportation mobile service. A number of 154 millennial computer science students as respondents are involved in this study. Their experience in using online mobile transportation services via smartphone was collected through an online questionnaire made using google forms and distributed via Facebook. The tool used in this study is Online User Experience Questionnaire (UEQ). The results showed that all UEQ categories scored in positive areas. The highest score is in the